2018
DOI: 10.15406/ijcam.2018.11.00398
|View full text |Cite
|
Sign up to set email alerts
|

Role of medicinal plants against Alzheimer’s disease

Abstract: Alzheimer's is an irreversible and dynamic neurodegenerative ailment which associated with the age and characterized by serious loss of memory, personality changes, uncommon behaviour and decrease in intellectual capacity. Till now no countermeasure available for Alzheimer's, however symptomatic treatment may enhance memory and other issues related to this disease. Products from natural resources such as medicinal plants have been utilized for the treatment of various memory disorders like amnesia, dementia, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 39 publications
0
33
0
2
Order By: Relevance
“…Furthermore, neuronal cell death caused by amyloid plaques was blocked by withanamide. Molecular modeling studies have shown that withanamide A and C attach uniquely to the active beta-amyloid pattern (Aβ 25–35) and block fibril formation [ 7 , 151 ].…”
Section: Therapeutic Implications Of Wa In Admentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, neuronal cell death caused by amyloid plaques was blocked by withanamide. Molecular modeling studies have shown that withanamide A and C attach uniquely to the active beta-amyloid pattern (Aβ 25–35) and block fibril formation [ 7 , 151 ].…”
Section: Therapeutic Implications Of Wa In Admentioning
confidence: 99%
“…Accordingly, these findings indicate that W. somnifera extracts, especially WA, reduce oxidative stress and mitochondrial dysfunction, and their beneficial role appears to be primarily based on their antioxidant properties [ 6 ]. Withanamides are a subset of these components that have been proven to scavenge free radicals produced at the time of the initiation and progression of AD [ 7 , 151 ].…”
Section: Therapeutic Implications Of Wa In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal therapy for AD has more advantages when compared to currently existing drug therapies with unavoidable side effects .it can also improve the patients' quality of life as they can be consumed as Nutraceuticals and even any slight increase in dose may not be a problem when consumed. In order to deliver these herbal formulations a proper route of administration must be selected so that they reach the site and show the therapeutic action Huperzia serrata [10,11,28,29] Lycopoidaceae 22,28,[30][31][32] .…”
Section: Cholinergic Hypothesismentioning
confidence: 99%
“…Most species of this Family are aromatic, presenting perineal with or without tuberous rhizomes, and most of them have medicinal properties (Larsen et al, 1998;Saensouk et al, 2016). Popularly, these plants are widely used as food, seasoning, and for the treatment of a wide range of diseases due to their antimicrobial, antioxidant (Chen et al, 2008), anti-inflammatory (Namsa et al, 2009), analgesic, nematicidal, vasorelaxant, sedative, antineoplastic, anti-allergic, healing (Umar et al, 2011), antitussive, anti-influenza, antiemetic, antidiarrheal, antidiabetic, anti-urinary incontinence activities (Kumar et al, 2011;Victório, 2011), and widely studied regarding its AD pharmacological effects (Monroy et al, 2013;Roy, 2018).…”
Section: Introductionmentioning
confidence: 99%